La Real Orden en el Despacho del rey: Secretarios, Presidentes y Validos - Francisco José Pérez Ramos (Historia. Instituciones. Documentos, 2012)
The Real Orden was created to communicate in an indirect way the commands that the king issued in his dispatch to the Councils, Boards, Courts and other authorities of the Monarchy. The professionals who assisted him in that task were enabled to transmit his provisions. In the sixteenth and seventeenth centuries, secretaries and court favourites used that power to come between the monarch and higher institutions. Despite the Real Orden has been associated with the Bourbon administration, it had been created and developed two centuries before under the Habsburg Monarchy.